2011
DOI: 10.1073/pnas.1107178108
|View full text |Cite
|
Sign up to set email alerts
|

The period of the circadian oscillator is primarily determined by the balance between casein kinase 1 and protein phosphatase 1

Abstract: Mounting evidence suggests that PERIOD (PER) proteins play a central role in setting the speed (period) and phase of the circadian clock. Pharmacological and genetic studies have shown that changes in PER phosphorylation kinetics are associated with changes in circadian rhythm period and phase, which can lead to sleep disorders such as Familial Advanced Sleep Phase Syndrome in humans. We and others have shown that casein kinase 1δ and ε (CK1δ/ε) are essential PER kinases, but it is clear that additional, unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(130 citation statements)
references
References 58 publications
(98 reference statements)
4
125
1
Order By: Relevance
“…For PER3, these polymorphisms are hypothesised to affect the promoter-driven gene expression levels of PER3 , or are hypothesised to alter the phosphorylation state of the PER3 protein by removal of potential Casein Kinase I (CKI) phosphorylation sites (Archer et al, 2003;Ebisawa et al, 2001). The latter is important because studies have shown that changes to the phosphorylation levels of PER protein can change circadian period (Lee et al, 2011). In addition, familial mutations in PER2 (Toh et al, 2001) and CKI (Xu et al, 2005) have been linked with advanced sleep phase disorder (ASPD) where it has been shown that greatly advanced circadian rhythms and sleep timing are due to changes in phosphorylation of PER protein.…”
Section: Genetic Basismentioning
confidence: 99%
“…For PER3, these polymorphisms are hypothesised to affect the promoter-driven gene expression levels of PER3 , or are hypothesised to alter the phosphorylation state of the PER3 protein by removal of potential Casein Kinase I (CKI) phosphorylation sites (Archer et al, 2003;Ebisawa et al, 2001). The latter is important because studies have shown that changes to the phosphorylation levels of PER protein can change circadian period (Lee et al, 2011). In addition, familial mutations in PER2 (Toh et al, 2001) and CKI (Xu et al, 2005) have been linked with advanced sleep phase disorder (ASPD) where it has been shown that greatly advanced circadian rhythms and sleep timing are due to changes in phosphorylation of PER protein.…”
Section: Genetic Basismentioning
confidence: 99%
“…1). Per1 must be phosphorylated by CK1-␦/ε to enter the nucleus (20). We (30,31) have previously shown that pharmacological inhibition of CK1-␦/ε using PF-670462 recapitulated the effects of Per1 knockdown, including increased levels of Cry2, decreased ␣-ENaC mRNA and protein expression, and, importantly, decreased ENaC channel activity.…”
Section: ␤-Hsd Expression Is Decreased After Per1 Knockdown In Nci-hmentioning
confidence: 99%
“…Transitions between the phosphorylated and dephosphorylated states can thus be important switches regulating biological activities (for example, switching transcription from on to off). In mammals, phosphoprotein phosphatase 1 (PPP1) dephosphorylates PER proteins, thereby antagonizing CKI-mediated PER degradation 15,51,52 (Fig. 2, state 2 to state 1).…”
Section: Multiple Modifications Antagonizing Per Degradationmentioning
confidence: 99%